2010
DOI: 10.1038/eye.2010.187
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and ocular imaging

Abstract: There exist ethnic differences in the prevalence of many ocular diseases. The ocular structures affected by these diseases can be imaged with devices that have increased in complexity over recent years. The purpose of this review is to explore what we mean by the term 'ethnicity' and what we know of ethnic differences in the structures of the eye that are commonly imaged. Finally, the implications of these ethnic differences are discussed in relation to the detection and monitoring of ocular disease that invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
3
12
1
Order By: Relevance
“…CFP is influenced by the pigmentation of the fundus. [ 11 ] Higher pigmentation of the fundus in our case due to ethnic difference from those described by Muftuoglu et al . may be a reason of smaller size of nevus on CFP compared to MCI.…”
Section: Discussioncontrasting
confidence: 41%
“…CFP is influenced by the pigmentation of the fundus. [ 11 ] Higher pigmentation of the fundus in our case due to ethnic difference from those described by Muftuoglu et al . may be a reason of smaller size of nevus on CFP compared to MCI.…”
Section: Discussioncontrasting
confidence: 41%
“…Studies have shown that retinal structures captured within color images as well as the phenotype and prevalence of some ocular diseases varied with ethnicity. 68,69 For example, pigmentation variations among ethnic groups can affect the observed ocular image. 70 Giancardo et al 71 have noticed that color retinal images of Caucasians have a strong red component whereas those of African Americans had a much stronger blue component.…”
Section: Illumination and Homogeneity Algorithms Analysismentioning
confidence: 99%
“…The Article describes a tested methodology using convolutional neural networks and its effectiveness in reading images from African patients. Although Bellemo and colleagues' final ensemble model had not been previously trained on African retinas, 7 which are more pigmented than Asian or white retinas, 8 the results they report are promising, showing the AI model and human graders to have similar outcomes in detection of referable diabetic retinopathy and systemic risk factor associations. The area under the curve of the AI system for referable diabetic retinopathy was 0·973 (95% CI 0·969-0·978), with corresponding sensitivity of 92·25% (90·10-94·12) and specificity of 89·04% (87·85-90·28).…”
Section: Artificial Intelligence For Diabetic Retinopathy Screening Imentioning
confidence: 95%